Echolocation of static and moving objects in two-dimensional space using bat-like frequency-modulation sound - Matsuo, Ikuo (Frontiers in Physiology, 2013)
Bats use frequency-modulated echolocation to identify and capture moving objects in real three-dimensional space. The big brown bat, Eptesicus fuscus, emits linear period modulation sound, and is capable of locating static objects with a range accuracy of less than 1 microsecond. A previously introduced model can estimate ranges of multiple, static objects using linear frequency modulation sound and Gaussian chirplets with a carrier frequency compatible with bat emission sweep rates. The delay time for a single object was estimated with an accuracy of about 1.3 microsecond by measuring the echo at a low signal-to-noise ratio. This model could estimate the location of each moving object in two-dimensional space. In this study, the linear period modulation sounds, mimicking the emitting pulse of big brown bats, were introduced as the emitted signals. Echoes were measured from moving objects at two receiving points by intermittently emitting these sounds. It was clarified that this model could localize moving objects in two-dimensional space by accurately estimating the object ranges.